A computational study for mechanical, thermoelectric and optoelectronic applications of BiAlO3 under static pressure. (September 2022) - Naeem Ullah, Hafiz Muhammad; Rizwan, Muhammad; Ali, Syed Shahbaz; Usman, Zahid; Ma, Xilan; Cao, Chuanbao
Abstract: Inorganic perovskites have a wide area of applications in low-cost optical and thermal applications. This manuscript aims to present Structural, mechanical, electronic, optical, as well as thermoelectric behavior of perovskite compounds BiAlO3 (BAO) for optoelectronic as well as thermoelectric applications, a novel energy production mechanism under high static pressure. Thermal stability is computed by enthalpy relation and also confirmed by elastic moduli. Physical properties are measured at ground state energy, and also explored pressure impact up to 100 GPa on electronic structure of BiAlO3. BAO shows an indirect band gap at 0–30 GPa, while it transforms to a direct with an increase in pressure. Mechanical stability was confirmed by applying Born's stability criteria. Even at higher pressure it remains in cubic phase and show mechanically stable structure. Optical responses are calculated and compared under pressure. With an increase in pressure, a clear blue shift was observed. The refractive index of refraction showed a decreasing trend from 3.32 to 2.84 from o to 100 GPa, respectively. Thermoelectric properties are explored by computing electric and thermal conductivity, Seebeck coefficient and power factor. The efficiency of the devices depends upon the figure of merit (ZT) i.e. the ratio of electrical to thermal conductivity must be small. The figure of merit indicated that at low temperature (lower than room temperature and normal pressure) the ZT can reach 0.7, if at high pressure, it can be larger than 0.8. Promising results of thermoelectric response under stress indicate that the said material is suitable for thermoelectric properties. BAO is not only led free but also environment friendly thus, the eventual candidate for devices based on optoelectronics and thermoelectric applications due to relevant bandgap nature after asserting pressure and its thermoelectric nature. Highlights: First-principles study of BiAlO3 semiconductor under influence of external stress. BiAlO3 shows cubic stability even higher pressure confirmed by Born's stability criteria. The Refractive index decreases from 3.32 to 2.84 and optical response results show a clear blue shift. The value of ZT reaches up to 0.8, making this material stunning for thermoelectric application.